College Football Overtime Outcomes: Implications for In-Game Decision-Making - Wilson, Rick L. (Frontiers in Artificial Intelligence, 2020)
Division I-A College Football adopted the present overtime rules for tie games in 1996. Rosen and Wilson (2007) used the first ten years of data to examine whether the typically chosen strategy of going on defense first was advantageous. At the time, results were mixed. Since that time, college football has transitioned to new offensive and defensive themes, but all coaches still opt for the same conventional wisdom strategy. This study validated that there is no advantage to the defense first strategy in overtime, and found that point spread (an indicator of team strength) and red zone offense performance of both teams were useful to predict game results. Examples are shown where a coach can use these relationships to influence end-of-regulation game decisions for teams considering whether to ‘settle’ for overtime or employ riskier “try to win” end game strategies.